"Only Image I Ever See": US media consumers' perceptions of Iraqis. (3rd July 2017) - Midberry, Jennifer
Abstract : Previous scholarship has demonstrated that Orientalist stereotypes pervade US and European photojournalism of the Middle East in general, and specifically of coverage of conflict, yet little work has investigated whether such ideology has been transmitted to audiences and incorporated into their personal worldviews. Therefore, this project investigates how media consumers negotiate Orientalist depictions of Iraqis. This qualitative analysis of focus group discussions between US college students at a large urban university sheds light on how media visuals shape consumers' perceptions about these groups. Understanding if and how Orientalist stereotypes are transmitted to audiences is an essential first step in trying to eliminate them from photography and from US society.